Demokrasi Antara Pembatasan Dan Kebebasan Beragama Serta Implikasinya Terhadap Formalisasi Islam - Hapsin, Abu (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
This paper discusses the relationship between democracy and freedom of religion. If democracy is defined as the freedom to behave as long as it is still in the constitutional frame, then the problem is whether to interpret democracy by formalizing religion in the political and legal order of a democratic country? The question rests on the assumption that religion has no rational domain so that the relationship between democracy and religious freedom sometimes becomes problematic when imposed on the constitutional domain. Theories of John Rawls and Franklin I. Gamwell as modern thinkers led to the conclusion that in certain areas religion cannot be forced into the political sphere, but universally religion is part of politics.